El modelo de enseñanza/aprendizaje de las ciencias en la reforma de las enseñanzas medias - Barandiaran Piedra, J. (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 2006)
In this paper the study of theoretical basis and educational assumptions of the proposals for experimental science contained in the «Project for the reform of the spanish educational system» is faced.